Chemical Constituents And Antimicrobial Activities Of Certain Plant Parts Of Sauropus Androgynus L - GAYATHRAMMA.K; K.V. PAVANI.; RAJI. R (International Journal of Pharma and Bio Sciences, 2012)
The antibacterial activity of leaves of Sauropus androgynus was evaluated on bacteria like Klebsiella pneumoniae, Bacillus cereus, Proteus vulgaris, Pseudomonas aeruginosa, Escherichia coli and Staphylococcus aureus. The solvents used for the extraction of plants were Petroleum ether, methanol, ethanol, and water. The in vitro antibacterial activity was determined by the disc diffusion method. Methanol and ethanol leaf extracts were more effective against pathogenic organisms, than other solvent extracts.